In vitro evaluation of aqueous weed extracts against Colletotrichum gloeosporioides, a causal agent of Colletotrichum leaf fall disease on rubber / Muhammad Afiq Abd Hamid - Abd Hamid, Muhammad Afiq (Faculty of Plantation and Agrotechnology, 2019)
Colletotrichum leaf fall disease (CLD) had become one of major disease on rubber in Malaysia. Colletotrichum gloeosporioides is the commonly fungal pathogen that caused this disease. The widespread of Colletotrichum gloeosporioides also not only focusing on rubber but also toward others crop such as citrus, cocoa, mango, papaya and many more. This is because the biological and cultural controls become inefficient for control this disease and currently depending on chemical used to handle it that can cause others problem such as environment problems. In this study, there were three replications for each type of weed species. Therefore, the main objectives of this study were to determine the antifungal activity of five selective weed extracts toward Colletotrichum leaf disease (CLD) on rubber using the in vitro experiment and to determine the most effective weed extract that can reduce growth of fungal activity. The total of five weed species was collected at Share farm in UiTM Jasin Campus, Melaka such as Solanum torvum, Lantana camara, Momordica charantia, Amaranthus viridis and Morinda elliptica. For antifungal activity, the technique that was used known as food poisoning technique. The weed extracts that showed the highest inhibitory effect of fungal growth was Solanum torvum with 86.79% of mycelial inhibition followed by Momordica charantia (18.54%), Amaranthus viridis (15.19%), Lantana camara (10.97%), and Morinda elliptica (5.91%) respectively. There are significant different between the diameter of fungal growth inhibition of weed species captured (p<0.05) through ANOVA analyze. Apart from that, the results identified the common weed species that has potential used as biological control agent for Colletotrichum gloeosporioides which was Solanum torvum.